Coal decarbonization: A state-of-the-art review of enhanced hydrogen production in underground coal gasification - Liangliang Jiang; Dan Xue; Zixiang Wei; Zhangxing Chen; Mammad Mirzayev; Yanpeng Chen; Shanshan Chen (Energy Reviews, 2022)
The world is endowed with a tremendous amount of coal resources, which are unevenly distributed in a few nations. While sustainable energy resources are being developed and deployed, fossil fuels dominate the current world energy consumption. Thus, low-carbon clean technologies, like underground coal gasification (UCG), ought to play a vital role in energy supply and ensuring energy security in the foreseeable future. This paper provides a state-of-the-art review of the world's development of UCG for enhanced hydrogen production. It is revealed that the world has an active interest in decarbonizing the coal industry for hydrogen-oriented research in the context of UCG. While research is ongoing in multiple coal-rich nations, China dominates the world's efforts in both industrial-scale UCG pilots and laboratory experiments. A variety of coal ranks were tested in UCG for enhanced hydrogen output, and the possibilities of linking UCG with other prospective technologies had been proposed and critically scrutinized. Moreover, it is found that transborder collaborations are in dire need to propel a faster commercialization of UCG in an ever-more carbon-conscious world. Furthermore, governmental and financial support is necessary to incentivize further UCG development for large-scale hydrogen production.